An Analysis of The Role of Affective Organizational Commitment in Mediating The Effects of Perceived Organizational Support and Motivation on Organizational Citizenship Behavior (A Case Study At The Ministry of Foreign Affairs) - Dewi Praptiwi; Corry Yohana; Agung Wahyu Handaru (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The gap in employee fulfillment among functional and executive positions at the Ministry of Foreign Affairs, along with the results of preliminary research, indicates suboptimal levels of organizational support, motivation, and employee participation. This study analyzes the role of Affective Organizational Commitment (AOC) in mediating the effects of Perceived Organizational Support (POS) and motivation on Organizational Citizenship Behavior (OCB) among civil servants at the Ministry of Foreign Affairs. A survey of 341 civil servants selected through proportionate stratified random sampling was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The outer model evaluation results showed that all indicators were valid and reliable (loading factors ranging from 0.716 to 0.840; Average Variance Extracted values ranging from 0.564 to 0.597; and Cronbach’s Alpha and Composite Reliability values above 0.70). The bootstrapping results demonstrated that POS and motivation had positive and significant effects on AOC (path coefficients of 0.426 and 0.394, respectively) and OCB (path coefficients of 0.191 and 0.288, respectively). Furthermore, AOC had a positive and significant effect on OCB (path coefficient = 0.407), representing the largest direct effect in the model. AOC was also found to significantly mediate the effects of POS (0.173) and motivation (0.161) on OCB, resulting in the acceptance of all seven research hypotheses. The research model explained 58.5% of the variance in AOC and 64.3% of the variance in OCB. These findings confirm that AOC serves as a psychological mechanism that translates organizational support and work motivation into organizational citizenship behavior. Therefore, the Ministry of Foreign Affairs is advised to simultaneously strengthen promotion fairness, employee welfare, and employees’ emotional attachment to the organization